Differential accumulation of vimentin fragments in preeclamptic placenta - Mary, Sheon; Kulkarni, Mahesh J.; Mehendale, Savita S.; Joshi, Sadhana R.; Giri, Ashok P. (Cytoskeleton, 2017)
Preeclampsia is a pregnancy complication that is the result of abnormal placentation because of inadequate trophoblast invasion into spiral arteries that prevent normal blood flow to the placenta. We report the alteration in vimentin protein proteolysis in placenta of normotensive and preeclamptic women, which is known to have a role in many physiological functions other than its major function in the structural integrity of the cell. Placental proteome from normotensive (n=25) and preeclamptic pregnancies (n=25) showed eight differentially accumulated protein spots of vimentin (proteolytic fragments) by two-dimensional electrophoresis. Immunoblots of normotensive and preeclamptic placenta revealed a difference in proteolytic processing of vimentin. In particular, lower molecular weight vimentin fragments of 32 and 20 kDa were 3.3 and 2.6-fold (p<0.0001) higher, respectively, in preeclampsia compared with normotensive placenta.